Double-balloon enteroscopy-assisted endoscopic retrograde cholangiography for Roux-en-Y reconstruction patients with papilla of Vater or bilioenteric anastomosis. (2nd January 2016) - Tsou, Yung-Kuan; Lee, Mu-Shien; Chen, Kuan-Fu; Lin, Cheng-Hui; Sung, Kai-Feng; Wu, Chin-Chieh
Abstract: Objective. Roux-en-Y reconstructions can be divided into intact papilla of Vater and bilioenteric anastomosis (BEA) with respect to endoscopic retrograde cholangiography (ERC). Double-balloon enteroscopy-assisted ERC (DBE-ERC) may produce different results between the two populations but lacks studies. Material and methods. Forty-seven patients with Roux-en-Y anastomosis undergoing 73 procedures of DBE-ERC were enrolled between July 2007 and August 2013. There were 14 patients with intact papilla of Vater (group A) and 33 patients with BEA (group B). The effectiveness of DBE-ERC, including data of reaching the blind end, performance of ERC, results of endoscopic therapies, and follow-up were retrospectively analyzed and compared between the two groups. Results. For reaching the blind end, the success rate was not different between the groups (85.7% vs. 81.8%, p = 0.7), but the mean procedure time was significantly shorter for group A (28 min vs. 52 min, p = 0.01). For ERC, the success rate was not different between the groups (91.7% vs. 96.3%, p = 0.53), but the mean procedure time was significantly longer for group A (28.4 min vs. 4 min, p < 0.001). All endoscopic therapies could be successfully performed in both groups. No group A patients and five (23.8%) group B patients developed recurrent biliary stricture/stones requiring interventions during a mean follow-up period of 26.1 months. Conclusions. DBE-ERC was effective for both populations with biliary disorders. Reaching the blind end was more difficult but ERC was easier for patients with BEA in terms of procedure time rather than success rates.